2017
DOI: 10.21873/anticanres.11779
|View full text |Cite
|
Sign up to set email alerts
|

Serum Heparin-binding Epidermal Growth Factor-like Growth Factor (HB-EGF) as a Biomarker for Primary Ovarian Cancer

Abstract: Ovarian cancer is the most lethal malignancy among gynaecological cancers. Although many anticancer agents have been developed for the treatment of ovarian cancer, it continues to have an extremely poor prognosis. Heparin-binding epidermal growth factor-like grown factor (HB-EGF) has been reported to be a rational therapeutic target for ovarian cancer. Here, we evaluated the clinical significance of serum HB-EGF by examining the association between prognosis and serum HB-EGF levels in patients with primary ova… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Increased expression of EGFR and mutations in its gene are associated with neoplasms such as non-small-cell lung cancer, glioblastomas, breast cancer, and head and neck squamous cell carcinoma (reviewed by Yarden and Pines, 2012). EGF family proteins have been documented as potential biomarkers for disease prognosis, and for progression of different tumor types (Briffa et al, 2015; Docea et al, 2013; Loupakis et al, 2014; Miyata et al, 2017; Olsen et al, 2012). Cancer therapies that inhibit EGFR signaling have been developed with beneficial results for patient lifespan; however, tumors ultimately acquire resistance to them, leading to the need for treatment change (Roskoski, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Increased expression of EGFR and mutations in its gene are associated with neoplasms such as non-small-cell lung cancer, glioblastomas, breast cancer, and head and neck squamous cell carcinoma (reviewed by Yarden and Pines, 2012). EGF family proteins have been documented as potential biomarkers for disease prognosis, and for progression of different tumor types (Briffa et al, 2015; Docea et al, 2013; Loupakis et al, 2014; Miyata et al, 2017; Olsen et al, 2012). Cancer therapies that inhibit EGFR signaling have been developed with beneficial results for patient lifespan; however, tumors ultimately acquire resistance to them, leading to the need for treatment change (Roskoski, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Miyata et al were able to confirm these results in a larger cohort and further proved that increased HB-EGF levels were associated with shorter PFS. However, a correlation between HB-EGF and histological subtype or HB-EGF and postoperative tumor residual could not be verified [ 38 ]. These results are in line with our findings.…”
Section: Discussionmentioning
confidence: 99%
“…For bladder cancer, HB-EGF was associated with reduced overall survival [ 37 ]. Miyata et al have already shown that HB-EGF is detectable in the serum of ovarian cancer patients and provides information about prognosis and tumor stage [ 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, related ErbB receptors may enhance the antidopaminergic actions implicated in the therapeutic mechanism of antipsychotic drugs. Recent studies have reported the abnormal expression of EGF in Parkinson's disease (11), autism (12,13), brain injury and limb fracture (14), gastric cancer (15), hepatocellular carcinoma (16,17), psoriasis (18), endometrial carcinoma (19), and primary ovarian cancer (20).…”
Section: Introductionmentioning
confidence: 99%